ANALISIS KEWAJIBAN PERPAJAKAN PADA PT ABC TAHUN 2020 - Jonathan, Vanessa; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to determine and analyze the tax obligations of income tax article 21, article 25, and article 4 paragraph 2 at PT ABC in 2020. Data collection techniques were obtained through interviews and documentation. The type of research used is a case study using quantitative methods. The results of this study indicate that PT ABC has carried out tax obligations such as reporting, paying, and withholding income tax article 21, article 25, and article 4 paragraph 2 in 2020 in full compliance with the tax provisions of Law Number 36 of 2008.